EFFECTIVE USE OF ELECTRICITY IN AGRICULTURE AND ITS IMPORTANCE - Axmadaliyev U.A.; Muhammadsobir Sobirjanov son of Ilgorjan (Лучшие интеллектуальные исследования, 2024)
Abstract This article describes the efficient use of electricity in agriculture and its importance.